Analisis Pengaruh U-Turn Terhadap Kinerja Ruas Jalan pada Jalan Hr Muhammad Surabaya - Rochmat, Muhammad Fikri Ar; Tjendani, Hanie Teki (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Main roads are public infrastructures that serve to connect various areas. With the increasing daily volume of transportation mode usage, infrastructure development has become a necessity, especially for land transportation facilities. HR. Muhammad Street is classified as a type 6/2 T road, with two lanes separated by a 2-meter-wide median; each lane is 2.5 meters wide for two lanes and 2 meters wide for one lane in each direction. The technique applied in this research is a quantitative method based on the PKJI 2023 guidelines. Information was obtained from both primary and secondary data. Primary data refers to information gathered from surveys, while secondary data refers to supporting information obtained from previous journals. The research findings indicate that the peak hours for vehicle U-turns are at 16:45 – 17:00 for passenger cars, 12:00 – 12:15 for heavy vehicles, and 16:15 – 16:30 for motorcycles. The peak vehicle volume occurs on Wednesday evenings from 16:00 to 18:00 WIB, where degree of saturation reaches 0.93, which falls into Level of Service E.